Avaliação da aprendizagem matemática: concepções e práticas de professores que lecionam no município de Estância (SE) - Anderson, Cynthia da Silva (2022)
In this research, we approach the evaluation that takes place in the school context aimed at improving the teaching-learning process, more specifically in Mathematics. Thus, we propose this research with a qualitative approach, which prioritizes the participants as the focus and the meaning of the lived experiences that were absorbed by them during their school life. The research makes use of the case study bias, which, according to Rodrigues (2017), consists of the detailed observation of a specific context, with the general objective of understanding the conceptions and evaluative practices of Mathematics teachers working in the final years of Elementary School, in two public educational institutions in the city of Estância (SE), about the assessment of learning in Mathematics. Regarding the theoretical-methodological procedures, the data generation instrument Balanço do Saber, created by Bernard Charlot (1996), was used, through which the teachers participating in the research told their memories in written narratives, describing facts of his student life that left marks both in his personal and professional life. In a second moment, after the construction of the text referring to the Balance of Knowledge, a semi-structured interview was applied. The research had the participation of two teachers and two Mathematics teachers, contributing with the interpretation and attribution of meanings to the data, according to qualitative studies. For the analysis of the generated data, the technique of content analysis was used from the perspective of Laurence Bardin (2016). To theoretically support this research, authors who discuss Learning Assessment and Mathematics Learning Assessment were used, such as D'Ambrósio (1993), Fiorentini (1995), Hoffmann (1994, 2000, 2012), Luckesi (2003; 2011; 2018), Samishima (2008) and Zabala (2014), among others. The research and its results indicate that the traditional conception of evaluation is still very present in the daily life of basic education schools. Mainly because traditional assessment is necessary, as well as classification and large-scale assessment, for example. Each fulfills its role in the educational context. In this sense, traditional assessment is important, as the model of the Brazilian education system requires tests to "prove" the student's learning, as well as the classification, which is essential for the student to be promoted to the next academic period through the status of a student. approved or fit. Likewise, large-scale evaluation has the function of collecting data and verifying the situation of national learning so that, from the information obtained, there are better subsidies for thinking about programs and policies for education. Each one has its function, but the assessment of learning as part of the didactic-pedagogical process still appears timid within the school and classrooms. Few teachers use it as a tool to help guide their daily pedagogical actions. In many cases, this does not happen out of ill will or disinterest. There are a number of situations that corroborate this scarcity in the use of learning assessment as a compass in the teaching-learning process. According to our research, it is a mixture that involves conceptions, practices and challenges that are interconnected and influence each other. However, some professors have already awakened to the importance of improving the evaluation practice, however, despite advances, reflections and some transformations, there is still inconsistency between theory and practice. What can be seen is that the conceptions that professors have about evaluation exert a great influence on their evaluative practice, in addition, with the research. It was possible to identify some of the main difficulties of these professors related to evaluation, ranging from emotional issues of students to the support of the school's pedagogical team.